USMON AZIM - Xosiyat Salayeva Fayzullayevna; Baxtiyarova Gozzal Maxmud qizi (TADQIQOTLAR, 2025)
Usmon      Azim  was  born  on  August  13,1950  in  the  Boysun  district  of Surkhandarya. His real name is Azimov Usmon. He graduated from the journalism faculty of Tashkent University. He worked as an editor, senior editor and deputy editor in chief of the  Republican Radio, executive secretary of the Tashkent regional branch of  the  Writer’s  Union  of  Uzbekistan.  Nowadays,  the  writer  is  mainly  engaged  in creative works. Usmon Azim won the literary community with his first book of poetry ,,Understanding  Man’’  published  in  1979.  Usmon  Azim-,,  People’s  poet  of Uzbekistan’’( 2000), as well as ,,The best of poetry’’ in the nomination of the best poetry of the year, and also won the ,, V. Mayakovskiy’’ Prize of Georgia. After the play ,,Nights without day’’ staged at the National Theater and won the title of ,, Best Performance’’  at  the  International  Theater  Festival  in  Andijan,  his  works  such  as ,,Bakhshiyona’’, ,,Strange Dragon’’, ,,Sadness’’,  ,,Long night’’ and ,,Glamour’’ prose collections  were  published.  Poems  and  epics  ,  which  are  included  in  dozens  of collections  of  his  work,  occupy  the  hearts  of  students  with   their  richness  of  vivid emotions, enthusiasm and charm, intensity and urgency. Sometimes pure, sometimes sad and caressing. At the same time, with its vitality, sharp drama and tragedy, it excites the  reader  and  excites  his  feelings.  His  works  have  been  translated  into  French, German, English, Polish, Estonian, Georgian, Macedonian, Lithuanian, Turkish, Tajik, Russian,  Kazakh,  Kyrgyz  and  other  languages.  In  turn,  Usman  Azim  translated samplaes of the works of dozens of poets, such as Eluard, Doglarja, Voznesenskiy, Vatseyetis, Marsinkyavichus into Uzbek. Many of the poet’s poems are sung by well-known hafiz and singers. The poet, who tried his hand at radio dramaturgy in the first period of his career (plays ,, Happy childhood’’,  ,,Plot for Documentary’’,  ,, Bahodir and Malika’’)  in later years began to write  dramas. His dramas ,, Nights without day’’,  ,, Return of Alpomish’’,  ,, One step way’’,  ,, Life of a writer’’ were staged. He was famous as the ,, Best playwright’’ in 1999 for his drama. ,,The return of Alpomish’’. The poet is also trying his hand at cinema. He wrote the screenplay for ,, Love’’ based on his story.